PERANAN GURU KELAS DALAM MENGATASI PERILAKU PERUNDUNGAN PADA SISWA KELAS IV SD INPRES TALABORONG KECAMATAN BAJENG BARAT KABUPATEN GOWA - Kasmawati; Syakur, Abdan; Madeamin, Rosmini (Almeera Education, 2025)
The type of research used in this research is descriptive qualitative research. The sample data sources in this study were grade IV teachers, grade IV students, and the principal of SD Inpres Talaborong. The data in this study were obtained through research instruments in the form of interviews, observation and documentation. The results of this study were tested for the validity of the data using source triangulation and technical triangulation. Based on the results of research at SD Inpres Talaborong in grade IV students, bullying is deviant behavior carried out by individuals or groups against other people or groups, which can cause physical or psychological harm. The type of bullying behavior in grade IV SD Inpres Talaborong students is physical bullying behavior such as hitting, pulling the headscarf, bouncing ties, pulling ears and so on. And verbal bullying like, calling parents names and making fun of them.Factors that cause bullying behavior in grade IV students are due to environmental factors, family factors, the economy and the community environment.